2014
DOI: 10.1055/s-0034-1371080
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping Technology in Orbital Floor Reconstruction: Application in Three Patients

Abstract: ).Rapid prototyping, also known as three-dimensional (3D) printing, is an additive manufacturing technology that allows expedient and accurate reproduction of osseous anatomy. It was originally introduced in the mechanical engineering field during the 1980s and this technology has gained interest in craniomaxillofacial surgery as a tool for assessment and preoperative surgical planning.1,2 For orbital floor fractures, rapid prototyping can provide an accurate anatomical representation of the osseous defect, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 8 publications
2
27
0
3
Order By: Relevance
“…Orbital cavity reconstruction is an ideal target of the RP technique owing to its anatomical complexity, and many researchers have applied a RP model to reconstruction [ 4 6 7 19 ]. Identifying an anatomical landmark is difficult in cases of large defects due to the thin orbital wall [ 7 15 19 ], Kozakiewicz et al [ 2 ] used an uninjured site as a mirrored RP model template to manufacture a pre-bent titanium implant when performing an orbital inferior wall fracture reconstruction. With a mirrored RP model, however, it was impossible to locate defects in the intraoperative field, and disagreement between the pre-bent titanium implant and the defect site may require the implant to be trimmed and redesigned, which increases the operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Orbital cavity reconstruction is an ideal target of the RP technique owing to its anatomical complexity, and many researchers have applied a RP model to reconstruction [ 4 6 7 19 ]. Identifying an anatomical landmark is difficult in cases of large defects due to the thin orbital wall [ 7 15 19 ], Kozakiewicz et al [ 2 ] used an uninjured site as a mirrored RP model template to manufacture a pre-bent titanium implant when performing an orbital inferior wall fracture reconstruction. With a mirrored RP model, however, it was impossible to locate defects in the intraoperative field, and disagreement between the pre-bent titanium implant and the defect site may require the implant to be trimmed and redesigned, which increases the operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Christopher et al found that direct intraoperative trimming and adaptation may take long operative time depending on the extension of the defect and experience of the surgeon when compared with stl models while preoperative rapid prototyping reduces the intraoperative time, risk of orbital mesh malposition, poor anatomical contour, and trauma to soft tissue because of multiple insertions during trimming and adaptation of the titanium mesh [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment protocol (►Fig. 2) was the same used by an earlier case report by Lim et al 1 Patients who sustained pure orbital floor fractures not involving the zygomatic complex, orbital rim, and/or the medial orbital wall were identified over a 12-month period. Orbital floor defects greater than 1 cm 2 was the parameter required for operative intervention.…”
Section: Methodsmentioning
confidence: 99%
“…1) leading to a reduction in treatment time, tissue trauma, and restoration of orbital form. 1,5 Hoelzle et al 6 were among the first to document the benefits of intraoperative scanning. It has since been used by some authors with the aim of eliminating malposition of implants and the need for revision surgery in midface trauma.…”
mentioning
confidence: 99%